2020
DOI: 10.1111/ggi.13980
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with falls among older persons in Malaysia

Abstract: Aim Falls are a common problem among older people, leading to major morbidity and increased mortality. The study aimed to determine the prevalence of falls among older persons in Malaysia and its associated factors. Methods Data were obtained from the National Health and Morbidity Survey 2018 (NHMS 2018), a cross‐sectional study using stratified cluster sampling design. Older persons were defined as aged ≥60 years in this study. Descriptive and logistic regression analyses were conducted using SPSS version 25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(77 reference statements)
1
5
1
Order By: Relevance
“…However, the fall rate was lower than that reported in domestic and foreign studies, such as those in America (37.5%) (Blackwood, 2019) Singapore (17.53%) (Gupta et al, 2017), Malaysia (18.7%) (Sahril et al, 2020) and India (29.1%) (Marmamula et al, 2020)…”
Section: Incidence Of Accidental Falls For Elderly Patients With Diab...contrasting
confidence: 54%
See 1 more Smart Citation
“…However, the fall rate was lower than that reported in domestic and foreign studies, such as those in America (37.5%) (Blackwood, 2019) Singapore (17.53%) (Gupta et al, 2017), Malaysia (18.7%) (Sahril et al, 2020) and India (29.1%) (Marmamula et al, 2020)…”
Section: Incidence Of Accidental Falls For Elderly Patients With Diab...contrasting
confidence: 54%
“…In our study period, incidence of accidental falls (9.79%) in elderly diabetic patients was consistent with a cross‐sectional study of 1002 elderly diabetes patients during 6 months in Shandong, China, 11.08% suffered accidental falls (Hong et al, 2020). However, the fall rate was lower than that reported in domestic and foreign studies, such as those in America (37.5%) (Blackwood, 2019) Singapore (17.53%) (Gupta et al, 2017), Malaysia (18.7%) (Sahril et al, 2020) and India (29.1%) (Marmamula et al, 2020). But notably, baseline data also showed that the incidence of falls of these patients in the past one year was 24.0%, which was similar to the above studies.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies reported that the prevalence of falls among OP was approximately 30% in England, Brazil, and Indonesia (Gale et al, 2018;Siqueira et al, 2011;Susilowati et al, 2020). In Malaysia, 24.3%-32.8% of OP residing in nursing homes (Ghazi et al, 2017;Hami et al, 2019;Kioh and Rashid, 2018) and 14.1%-19.7% community-dwelling OP had fallen (Alex et al, 2018;Hami et al, 2019;Ibrahim et al, 2017;Sahril et al, 2020). Fall-related injuries such as fractures, hematoma, and severe laceration are the main consequences of falls that can result in disability, activity limitation, and dependency (Berg and Cassells, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Most happen between midnight and noon, possibly due to nighttime toileting and increased morning activity (Ministry of Health Malaysia, 2019). In the Malaysian community, it was revealed that one of every six older Malaysians had experienced at least one fall within the previous 12 months (Sahril et al, 2020).…”
Section: Introductionmentioning
confidence: 99%